Management leadership and labor satisfaction of the teachers of the National University Hermilio Valdizan 2017 - Cavalie-Martel, Karina P. (2019)
The present investigation examined the level of job satisfaction of the UNHEVAL teacher in relation to the leadership style in the reality of an educational institution in the district of Huánuco. The objective was to know the level of job satisfaction of teachers with respect to the perception of the type of managerial leadership exercised by the Directors. The method, 237 teachers were surveyed after signing the informed consent, using the Rensis Likert questionnaire for leadership styles and the Scale of Opinions SL-SPC questionnaire for job satisfaction, was a relational level study, basic type, transversal analytical, quantitative approach , descriptive and analytical statistics (Pearson's chi-square) were used for the data processing in the statistical program SPSS version 24. The results showed that the perception of teachers about the type of leadership, in 37.6% They rarely perceived participatory leadership. In 18.1% always the coercive authoritarian leadership, followed with 13.1 always the consultative leadership, and in a lower percentage 7.6% perceived the benevolent authoritarian leadership. When applying the Chi-square test of Pearson, it was determined that there is a relationship between the consultative leadership and the job satisfaction of the teachers of the National University Hermilio Valdizán, whose value p = 0.000 (p <0.05). There is also a relationship between advisory leadership, benevolent authoritarian and coercive authoritarian and job satisfaction of teachers of the National University Hermilio Valdizán, whose value p = 0.000 (p <0.05). It was concluded that there is a statistically significant relationship between Management Leadership Style and the job satisfaction of the professors of the National University Hermilio Valdizán 2017.